1980
DOI: 10.1002/ijc.2910250209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the humoral response of glioma patients to a possible common tumor‐associated antigen(S)

Abstract: Cytotoxic antibodies against glioblastoma-associated antigen(s) have been sought for in glioma patient sera. Complement-dependent cytotoxicity (CDC) I and antibody-dependent cell-mediated cytotoxicity (ADCC) assays were used to test sera from 80 patients using 51 Cr labelled target cells derived from eight different glioblastoma lines. As more positive sera were detected with ADCC than with CDC, ADCC assay was used for the remainder of the study. Cytotoxic antibodies were detected in the sera from 8 of 80 glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In other studies using large numbers of patients, the antiglioma activity has been demonstrated to extend to other neuroectodermal tumors and to connective tissue. This antiglioma activity can be readily absorbed out of the serum of these patients by cells of other tumors and by platelets [23]. Therefore, it has been suggested that while there is an autologous response by the humoral immune system in patients with CNS gliomas, this response is not specific and therefore does not constitute a direct antitumoral response.…”
Section: Humoral Immune Responsementioning
confidence: 98%
See 1 more Smart Citation
“…In other studies using large numbers of patients, the antiglioma activity has been demonstrated to extend to other neuroectodermal tumors and to connective tissue. This antiglioma activity can be readily absorbed out of the serum of these patients by cells of other tumors and by platelets [23]. Therefore, it has been suggested that while there is an autologous response by the humoral immune system in patients with CNS gliomas, this response is not specific and therefore does not constitute a direct antitumoral response.…”
Section: Humoral Immune Responsementioning
confidence: 98%
“…Populations of B lymphocytes are present within gliomas, but their ability to produce anti-glioma antibodies capable of participating in complement dependent or antibody dependent cell-mediated cytotoxic responses is doubtful [1,23]. Several laboratories have demonstrated the presence of limited antiglioma activity within the sera of a small number of patients harboring CNS gliomas [7,21,26,36].…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…Recently Martin-Achard et al [27], in a critical re-evaluation of the humoral response of glioma patients to a possible common tumour-associated antigen, found cytotoxic antibodies in sera from 8 of 80 glioma patients (10%) as tested by CDC. With the more sensitive antibody-dependent cell-mediated cytotoxicity assay (ADCC), 20 of 143 patients' sera (14%) contained cytolytic antibodies.…”
Section: Glioma-associated Antigens Defined By Patients' Humoral or Cmentioning
confidence: 98%
“…The existence of an autologous or allogenic response against a glioma tumor antigen has been investigated by Martin-Achard et al [37] who looked for cytotoxic antibodies against glioma-associated antigens in the sera from 80 patients using both complement-dependent cytotoxicity (CDC) and antibody-dependent cell-mediated cytotoxicity (ADCC) assays. CDC revealed the presence of cytotoxic antibodies in the sera of 10~ while ADCC was seen in 14~ of the patients.…”
Section: Glioma-associated Antigensmentioning
confidence: 99%